Expression of rice siR109944 in Arabidopsis affects plant immunity to multiple fungal pathogens. (2nd April 2020) - Qiao, Lulu; Zhao, Hongwei; Jin, Hailing; Niu, Dongdong
ABSTRACT: Plant small RNA (sRNA)-mediated gene expression has a conserved role in regulating plant growth, development, and immunity. Heterologous expression of sRNA contributes to determining whether the function of sRNA is conservative or independent. We recently characterized the Tourist-miniature inverted-repeat transposable element (MITE)-derived siR109944 had a conserved function that enhanced susceptibility to Rhizoctonia solani infection by affecting auxin homeostasis in rice and Arabidopsis . To ascertain whether the function of rice siR109944 has a broad-spectrum immunity in Arabidopsis, we infected Arabidopsis with a variety of fungal pathogens. Overexpression of siR109944 in Arabidopsis increased susceptibility to Botrytis cinerea, Sclerotinia sclerotium, and Verticillium dahliae infection. Further studies found that Arabidopsis auxin-related miRNAs were suppressed in siR109944 OE . Our results demonstrated that overexpression of rice siR109944 in Arabidopsis affected immune responses to multiple pathogens by inhibiting auxin-related miRNA expression in planta .